Durability of Springs - Kobelev, Vladimir (Springer International Publishing, 2018)
This book offers an advanced treatise of the mechanics of springs with focus on the springs for automotive industry. It demonstrates new and original results for the optimization of helical springs as well the design of disk springs and thin-walled springs and presents the new results for creep and relaxation of springs made of steel under high static loads. The fatigue of springs and weak link concept for cyclically loaded springs are enlightened. The closed form solutions of advanced problems allow the deeper understanding of spring mechanics and optimization of energy harvesters.